Wood adhesives in Malaysia / Zuraini Othman - Othman, Zuraini (2007)
Wood adhesives are an important element in wood based processing industries in Malaysia. There are many types of adhesives that use follow the types of products to produce in wood based industries. The properties of adhesives are different and it is using for suitable application follow the properties. Quality and bonding strength for each adhesive also different and it determine by specific tests.